Psychological Disturbances and Quality of Life in Obese and Infertile Women and Men - Piotr Kocełak; Jerzy Chudek; Beata Naworska; Monika Bąk-Sosnowska; Barbara Kotlarz; Monika Mazurek; Paweł Madej; Violetta Skrzypulec-Plinta; Piotr Skałba; Magdalena Olszanecka-Glinianowicz (International Journal of Endocrinology)
Anovulatory cycles and endometriosis are the main causes of female infertility. The most frequently anovulatory cycles are related to polycystic ovary syndrome (PCOS) commonly associated with obesity and hormonal disturbances in the course of obesity. Recently published studies revealed that infertility affects about one in six couples during their lifetime and is more frequent in obese. Obesity is also associated with male infertility related to erectile dysfunction, hormonal disturbances and lower semen quality. Any of these above mentioned disorder is the important risk factor of psychological disturbances and poor quality of life among women and men in the reproductive age. On the other hand the mood disorders may exacerbate the hormonal disturbances and worsen the effectiveness of infertility management. Infertility, its therapy with accompanying psychological disturbances may also significantly affect the partners relationships. The review summarize the results described in the current literature on the association between obesity and infertility and psychological disturbances as well as their impact on quality of life and sexual functioning in women and men. Moreover, the impact of infertility and psychological disturbances on partners relationships is discussed.